2016
DOI: 10.1007/s11356-016-8194-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoids are key players in the antioxidant defense to ozone of European ash, Fraxinus excelsior

Abstract: Physiological and biochemical responses to ozone (O) (150 ppb, 8 h day, 35 consecutive days) of two Italian provenances (Piedmont and Tuscany) of Fraxinus excelsior L. were evaluated, with special attention to the role of phenylpropanoids. Our results indicate (i) the high O sensitivity especially of Piedmont provenance (in terms of visible injury, water status, and photosynthetic apparatus); (ii) although the intra-specific sensitivity to O between provenances differs (mainly due to different stomatal behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…This outcome may confirm the key role of flavonoids in ROS scavenging under chronic O 3 -induced oxidative stress (Cheynier et al, 2013;Cotrozzi et al, 2018). These cultivar-specific fine regulations of the phenolic metabolism adopted by plants to cope with O 3 stress trough time was confirmed by the several significant correlations among compounds.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This outcome may confirm the key role of flavonoids in ROS scavenging under chronic O 3 -induced oxidative stress (Cheynier et al, 2013;Cotrozzi et al, 2018). These cultivar-specific fine regulations of the phenolic metabolism adopted by plants to cope with O 3 stress trough time was confirmed by the several significant correlations among compounds.…”
Section: Discussionsupporting
confidence: 62%
“…Among non-enzymatic antioxidant systems, it has been reported that phenolic compounds have a great efficacy (Cheynier, Comte, Davies, Lattanzio, & Martens, 2013;Cotrozzi et al, 2018;Pellegrini et al, 2018aPellegrini et al, , 2018bPellegrini et al, , 2019. Phenolic compounds are usually arranged in two groups-simple phenols (such as the cinnamic, p-coumaric, syringic and salicylic acids) and more complex molecules, often containing aromatic rings linked together (Kulbat, 2016).…”
mentioning
confidence: 99%
“…Activated PSC metabolism (increased biosynthesis and reduced turnover) explains the increased concentrations of phenolic and terpenoid PSCs in tree foliage found in a meta-analysis ( Valkama et al, 2007 ). In response to O 3 treatment, elevated levels of total phenolics ( Gao et al, 2016 ), condensed tannins ( Couture et al, 2017 ) and flavonoids ( Cotrozzi et al, 2018 ) were found in foliage of deciduous trees, but this was not the case in needles of coniferous trees ( Riikonen et al, 2012 ).…”
Section: Responses To Abiotic Factors – Psc Concentrations In Treesmentioning
confidence: 98%
“…The same team (Hoshika et al 2017b) investigated in a free-air controlled exposure facility the ozone doseresponse relationships for three European oak species under a range of soil water availability. Physiological and biochemical responses to long-term exposure to ozone of two Italian provenances of Fraxinus excelsior were the focus of the paper presented by Cotrozzi et al (2017a). Pellegrini et al (2017) reported about the detoxification mechanisms underlying ozone sensitivity in tulip tree, Liriodendron tulipifera and Cotrozzi et al (2017b) talked about the comparison between an evergreen isohydric oak species (Quercus ilex) and a sympatric, deciduous and anisohydric species (Q. pubescens) under long-term ozone stress.…”
mentioning
confidence: 99%